2007
DOI: 10.1093/aob/mcm149
|View full text |Cite
|
Sign up to set email alerts
|

QTL Mapping of Domestication-related Traits in Soybean (Glycine max)

Abstract: Background and AimsUnderstanding the genetic basis underlying domestication-related traits (DRTs) is important in order to use wild germplasm efficiently for improving yield, stress tolerance and quality of crops. This study was conducted to characterize the genetic basis of DRTs in soybean (Glycine max) using quantitative trait locus (QTL) mapping.MethodsA population of 96 recombinant inbred lines derived from a cultivated (ssp. max) × wild (ssp. soja) cross was used for mapping and QTL analysis. Nine DRTs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
241
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(259 citation statements)
references
References 53 publications
17
241
1
Order By: Relevance
“…3d and Supplementary Fig. 11b), respectively 21 .We also detected a GWAS signal responsible for purple or white flower color at the W1 locus 22 and a GWAS signal corresponding to seed coat color variation at the I locus [23][24][25] . We found that these two signals underwent selection during domestication and improvement, respectively (Supplementary Fig.…”
Section: Supplementary Tables 8 and 9)mentioning
confidence: 53%
See 1 more Smart Citation
“…3d and Supplementary Fig. 11b), respectively 21 .We also detected a GWAS signal responsible for purple or white flower color at the W1 locus 22 and a GWAS signal corresponding to seed coat color variation at the I locus [23][24][25] . We found that these two signals underwent selection during domestication and improvement, respectively (Supplementary Fig.…”
Section: Supplementary Tables 8 and 9)mentioning
confidence: 53%
“…In our analyses, selection signals were detected in almost all reported domestication-related QTL regions 21 ( Fig. 3 and Supplementary Table 10).…”
Section: Supplementary Tables 8 and 9)mentioning
confidence: 66%
“…Therefore, the inverse correlation between the small sizes of these characters and the shattering resistance, which was found by Tiwari and Bhatia (1995), might reflect no more than the differences between the wild and cultivated species. Another plausible explanation is that other QTLs conditioning shattering resistance were involved in the genotypic differences found in the previous studies, although several shattering-resistant cultivars besides Hayahikarirelated ones are likely to harbor shattering-resistance alleles at qPDH1 as well (Bailey et al, 1997;Funatsuki et al, unpublished results) and this QTL seems to have played a role in the domestication process (Liu et al, 2007).…”
Section: Discussionmentioning
confidence: 84%
“…& Zucc., which scatters its seeds via pod dehiscence (Hymowitz and Singh, 1987). Although in general, soybean (G. max) is more resistant to pod dehiscence (shatteringresistant) than G. soya (Liu et al, 2007), significant genetic variation has been found among soybean cultivars (e.g. Tsuchiya, 1986;Romkaew and Umezaki, 2006).…”
mentioning
confidence: 99%
“…In 2008, three suggestive QTL were detected on chromosomes 10, 18, and 20 (Table 3). Suggestive QTL were those QTL possessing peaks in LOD scores that did not exceed the genome wide threshold, but on the chromosome level were at or exceeded significant P \ 0.05 (Liu et al 2007;Tiwari et al 2009;Willems et al 2010). The LOD scores of these QTL ranged from 2.6 to 2.9 and the variation explained was 11.9-19.4 %.…”
Section: Total P Determinationmentioning
confidence: 99%